How environmental treaties contribute to global health governance - Jean-Frédéric Morin; Chantal Blouin (BMC, 2019)
Abstract Background Recent work in international relations theory argues that international regimes do not develop in isolation, as previously assumed, but evolve as open systems that interact with other regimes. The implications of this insight's for sustainable development remains underexplored. Even thought environmental protection and health promotion are clearly interconnected at the impact level, it remains unclear how global environmental governance interacts with global health governance at the institutional level. In order to fill this gap, this article aims to assess how environmental treaties contribute to global health governance. Methods and results To assess how environmental treaties contribute to global health governance, we conducted a content analysis of 2280 international environmental treaties. For each of these treaties, we measure the type and number of health-related provisions in these treaties. The result is the Health and Environment Interplay Database (HEIDI), which we make public with the publication of this article. This new database reveals that more than 300 environmental treaties have health-related provisions. Conclusions We conclude that the global environmental regime contributes significantly to the institutionalization of the global health regime, considering that the health regime includes itself very few treaties focusing primarily on health. When reflecting on how global governance can improve population health, decision makers should not only consider the instruments available to them within the realm of global health institutions. They should broaden their perspectives to integrate the contribution of other global regimes, such as the global environmental regime.